CASE STUDY ON THE NEEDS ANALYSIS OF VOCATIONAL MEDICAL LAB STUDENTS AT THE NATIONAL INSTITUTE FOR TECHNOLOGY - Ali Mahmood Mahmood, Hemn Mohammed (PUPIL: International Journal of Teaching, Education and Learning, 2024)
The development of vocational education programs in Kurdistan is considered a potential solution to enhance the region’s human resources. This development is closely linked to the development of English language proficiency in Kurdistan. The Ministry of Higher Education and Scientific Research has focused on enhancing the communicative abilities of vocational education students in English, particularly in listening, reading, writing, and speaking. This study examines the needs assessment of English for Specific Purposes (ESP) courses for educational students, aiming to identify learning objectives and needs. Data were gathered through questionnaires and interviews, revealing that students face difficulties in active communication skills (40%), grammar (15%), reading comprehension (25%), content comprehension (10%), and writing (10%). Specific areas of English language use in technology were identified, including English media (40%), crosswords (20%), dialogue content (20%), and multiple-choice exercises (20%). The study’s findings contribute to understanding the learning requirements and objectives necessary for effective English language education. They emphasize the importance of addressing students’ reading, writing, grammar, and other requirements to prepare them for future challenges.